Bedding for dairy cows: risk factors associated with mastitis occurrence and management strategies - Freu, Gustavo (2024)
Bovine mastitis is a common and costly disease in dairy herds. Strategies to control mastitis occurrence include understanding the risk factors and causes, as well as identifying measures to reduce udder exposure to pathogens. To address these topics, this thesis was organized into three studies. The first study characterized the frequency and profile of pathogens isolated from clinical (CM) and subclinical (SCM) mastitis in dairy cows housed in compost-bedded pack barn (CB), aiming to evaluate the association between mastitis occurrence and bedding characteristics in CB systems. Over six months, seven dairy herds were visited monthly for milk and bedding sample collections. Our results showed that Escherichia coli and environmental streptococci were the most frequently isolated pathogens from CM cases, while Staphylococcus chromogenes and contagious pathogens were the mostly isolated from SCM cases. We also demonstrated that bedding physical-chemical (specifically moisture, carbon to nitrogen ratio) and microbiological characteristics affect the mastitis occurrence in dairy cows housed in the CB system. The second study investigated the effect of a lime-based conditioner (LBC), at different concentrations (0, 10, 15, and 20%), on the physical-chemical and microbiological characteristics of anaerobically digested manure solids (ADMS) and separated raw manure solids (SRMS). Untreated ADMS and SRMS were assessed for dry matter (DM) content, pH, and microbiological counts immediately after LBC treatment (0 h) and at 24, 72, and 168 h of storage at 28ºC. It was observed a linear increase in both DM and pH with increasing LBC concentration. On the other hand, a linear decrease in bacterial counts was observed with increasing LBC concentration, highlighting the potential of LBC to control pathogen proliferation in manure-derived bedding. The third study evaluated retrospective data from six years to determine the speciation and distribution of non-aureus staphylococci and mammaliicocci (NASM) isolated CM cases. Twenty-nine NASM species were identified from bovine CM cases, with S. chromogenes, S. haemolyticus, S. simulans, S. epidermidis, Mammalicoccus sciuri, S. agnetis/S. hyicus, S. borealis, and S. xylosus being the eight most prevalent NASM species. A similar NASM distribution was observed across seasons, even though large variability in the isolation frequency between the eight most prevalent NASM was observed according to season and year. The results of this thesis may assist consultants and dairy farmers in developing strategies for bedding management and mastitis control.